Sosialisasi Keselamatan Dan Kesehatan Kerja (K3) Pada Instalasi Videotron Di Universitas Pembangunan Panca Budi - Beni Satria; Pristisal W; Amani d tarigan (Cattleya Darmaya Fortuna, 2024)
A videotron is a display panel that uses LED technology to show images, videos, or other moving content. There are two types of videotrons: indoor and outdoor. Indoor videotrons are used indoors, while outdoor videotrons are used outdoors. Videotrons have many functions, one of which is as an advertising medium. They can be used to promote products, services, or brands, as well as to convey information or messages to the public. In the installation of videotrons, occupational safety and health issues must be considered by the operators to avoid workplace accidents. Electrical safety and health (K3) is a management system aimed at protecting workers and the general public from electrical hazards that could potentially cause accidents and health problems. Electrical hazards can include electric shock, fire, and explosions. Some activities that can be conducted to implement K3 in the electrical field include: Understanding electrical hazards: Workers and the general public need to understand electrical hazards to take appropriate preventive measures. Implementation of safety standards: Companies need to apply safety standards established by the government or relevant organizations. Use of personal protective equipment (PPE): Workers need to use appropriate PPE to protect themselves from electrical hazards. Maintenance of electrical equipment: Electrical equipment needs to be routinely maintained to ensure that it functions properly and safely.Implementing K3 in the electrical field is essential to prevent accidents and health issues caused by electricity. Electrical accidents can lead to material losses and casualties.